Surprising comparative properties of monetary models: Results from a new model database - John B. Taylor; Volker Wieland (European Central Bank (ECB), 2010)
In this paper we investigate the comparative properties of empirically-estimated monetary models of the U.S. economy. We make use of a new database of models designed for such investigations. We focus on three representative models: the Christiano, Eichenbaum, Evans (2005) model, the Smets and Wouters (2007) model, and the Taylor (1993a) model. Although the three models differ in terms of structure, estimation method, sample period, and data vintage, we find surprisingly similar economic impacts of unanticipated changes in the federal funds rate. However, the optimal monetary policy rules are different in the different models. Simple model-specific policy rules that include the lagged interest rate, inflation and current and lagged output gaps are not robust. Some degree of robustness can be recovered by using rules without interest-rate smoothing or with GDP growth deviations from trend in place of the output gap. However, improvement vis-à-vis other models, comes at the cost of significant performance deterioration in the original model. Model averaging offers a much more effective strategy for improving the robustness of policy rules.
Keywords: E12; E52; E61; 330; Model uncertainty; monetary policy rules; Monetary policy transmission; New-Keynesian models; Robustness; Geldpolitik; Wirkungsanalyse; Messung; Wissenschaftliche Methode; Ökonometrisches Modell; Bewertung; USA